Evaluation of disorders of adaptive mechanisms in heart failure by microwave dielectrometry - Khmil, N.V.; Kolesnikov, V.G.; Altuhov, O.L. (Radiotekhnika, 2022)
Differential diagnosis of stress adaptive mechanisms is one of the areas of modern biomedical engineering and the most complex part of the pre-nosological diagnosis of cardiac pathology. One of the manifestations of disadaptation in heart failure is a violation of the mechanisms of realization of the intracellular chain "signal-function". The concept of imbalance in the functioning of the adenylate cyclase system and β-adrenergic receptors of the erythrocytes membrane and cardiomyocytes is considered in the pathogenesis of the heart. The study of the dielectric constant (ε՜) of erythrocytes of patients with heart failure was performed using an instrument-recording complex based on microwave dielectrometry of the γ-dispersion region of free water dielectric permittivity. Testing of the β-adrenergic complex of the erythrocyte membrane by specific stimulators, blockers, and modulators was implemented at a fixed frequency of microwave radiofrequency generation (f = 37,7 GHz). Interpretation of the obtained experimental data was that the process of interaction of bioregulators with the biological system is accompanied by an increase or decrease in the relative amount of free water, which leads to a change in the real part of ε՜ complex dielectric constant. This allowed us to visualize the violation of the signal cell system at the molecular level, which manifested itself in the change of integral hydration by ε՜ parameter. It was shown that the change in the dielectric constant of the erythrocyte suspension at risk (patients with hereditary predisposition to dilated and ischemic cardiomyopathy) was significant relative to the dielectric parameters of erythrocyte samples from healthy donors; there was a tendency to block β-adrenergic receptors, with the combined action of adrenaline, PGE2 and cordanum, with Δε՜ = 0,009 ± 0,008 х 10-12 F/m. It should be noted the formation of preconditions for changes in the functioning of the adenylate cyclase system and the development of heart failure in the group at risk, is accompanied by dilated and ischemic cardiomyopathy. The effectiveness of the microwave dielectrometry method for the assessment of violations of adaptation mechanisms through the adenylate cyclase system of the erythrocyte membrane in dilated and ischemic forms of cardiomyopathies is shown. The results of the study are the basis for the introduction of the dielectric constant criterion in the general algorithm of pre-nosological diagnosis of heart failure.